2013
DOI: 10.5423/ppj.oa.10.2012.0156
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Guava Plants to Inoculation with Arbuscular Mycorrhizal Fungi in Soil Infested with Meloidogyne enterolobii

Abstract: In the Northeast of Brazil, expansion of guava crops has been impaired by Meloidogyne enterolobii that causes root galls, leaf fall and plant death. Considering the fact that arbuscular mycorrhizal Fungi (AMF) improve plant growth giving protection against damages by plant pathogens, this work was carried out to select AMF efficient to increase production of guava seedlings and their tolerance to M. enterolobii. Seedlings of guava were inoculated with 200 spores of Gigaspora albida, Glomus etunicatum or Acaulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
4
6
1
5
Order By: Relevance
“…Generally, it has been shown that plants infected with Meloidogyne undergo more growth when their roots are associated with AMF (Sharma & Sharma, 2017a;Campos, 2020). The trends in our study corroborate those found by Campos et al (2013) who investigated the effects of the same AMF species on guava plants. However, the plants used by Campos et al (2013) were rooted cuttings and only the A. longula treatment yielded significant results, whereas, in the present study, the guava plants were grown from seed, and all the AMF species tested were found to promote growth (table 3).…”
Section: Meloidogynesupporting
confidence: 91%
“…Generally, it has been shown that plants infected with Meloidogyne undergo more growth when their roots are associated with AMF (Sharma & Sharma, 2017a;Campos, 2020). The trends in our study corroborate those found by Campos et al (2013) who investigated the effects of the same AMF species on guava plants. However, the plants used by Campos et al (2013) were rooted cuttings and only the A. longula treatment yielded significant results, whereas, in the present study, the guava plants were grown from seed, and all the AMF species tested were found to promote growth (table 3).…”
Section: Meloidogynesupporting
confidence: 91%
“…On the other hand, the greatest guava plant growth obtained from seeds and inoculated with different species and the arbuscular mycorrhizal fungus combination has been reported previously (Estrada-Luna et al, 2000;Schiavo and Martins, 2002;da Silva-Campos et al, 2013;Mohandas et al, 2013;Das et al, 2017). In general, this study found an increase in guava plants propagated by seeds when a mycorrhizal consortium was applied.…”
Section: Guava Plant Growthsupporting
confidence: 67%
“…Por otro lado, el mayor crecimiento de plantas de guayaba obtenidas de semilla e inoculadas con diferentes especies y combinaciones de HMA ya ha sido reportada previamente (Estrada-Luna et al, 2000;Schiavo y Martins, 2002;da Silva-Campos et al, 2013;Mohandas et al, 2013;Das et al, 2017). En general, en este trabajo se encontró un aumento en el crecimiento de las plantas de guayaba propagadas por semilla cuando se les aplicó algún consorcio micorrízico.…”
Section: Guava Plant Growthunclassified
See 1 more Smart Citation
“…Interactions among AMF, plants, and nematodes are complex, and the nature and effects of these interactions depend on the species (Castillo et al, 2006; Hol and Cook, 2005) and the environmental conditions involved (Calvet et al, 2001). The effects of AMF on the growth of plants infected with Meloidogyne nematodes vary, but are generally positive (Borowicz, 2001; Campos et al, 2013; Maia et al, 2006). …”
mentioning
confidence: 99%